Measurability of the mathematics teaching modules on problem solving-skills in the concentration of agribusiness expertise in plantation - Sudiansyah, Sudiansyah; Rif'at, Mohamad; Hartoyo, Agung (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
Preliminary research involving 30 mathematics teachers at the MGMP VHS of Ketapang district and interviews with business world and plantation industry representatives suggested that 81.7% of respondents voiced concerns over the current mathematics teaching materials, which do not adequately equip students with problem-solving skills in line with their expertise concentration. This issue reflects on the quality of VHS graduates who are expected to be job-ready and skilled. The objective of this study is to develop a measurable teaching module, conceptually and methodologically, that yields quantifiable results in alignment with the concentration of expertise and the requirements of the business and industry world. The research method adopted is a mixed method with a sequential explanatory design through the Van den Akker development study. A quantitative analysis of 20 respondents, comprising mathematics and productive teachers at a center of excellence vocational school, lecturers of Tanjung Pura STKIP, Ketapang State Polytechnic, and a team from the business and industry world in the plantation sector, resulted in a Pearson correlation of Ryx1x2x3=0.949, a determination coefficient [r2] of 0.900, and an F-calculation of 48.06 for the regression equation Y ̂ = 0.566 + 0.444 X1 + 0.278 X2 + 0.135 X3. From these results, it is concluded that the concepts, methods, and outcomes utilized in this teaching module are appropriate. The relationship between concepts, methods, and outcomes in teaching modules on skills to solve mathematical problems is unidirectional. Expert validity on aspects of module content, presentation feasibility, language appropriateness, and problem-solving skills amounted to 96.88% in the Very Valid category. Practicality from the aspects of interest, material, and language places the category at 92.02, which is very practical